A consistent framework for chemo-mechanical cohesive fracture and its application in solid-state batteries. (December 2021) - Rezaei, Shahed; Asheri, Armin; Xu, Bai-Xiang
Abstract: Damage and fracture can be induced not only by mechanical loading but also due to chemical interactions within a solid. On one hand, species concentration may embrittle or toughen the material and on the other hand, the mechanical state adds additional driving force for diffusion. We propose a chemo-mechanically coupled cohesive fracture model with several novel features. It distinguishes the mode-dependent damage progression and its influence on lithium transport. Coupled with mode-dependent cohesive zone damage, the model recaptures both the normal and tangential transport behavior of lithium at the interface. Moreover, it tackles concentration-dependent crack initiation, various softening behavior, as well as the cyclic damage accumulation. The thermodynamic consistency of the proposed model with the mentioned features is demonstrated. The model is numerically implemented with the finite element method. Numerical results, along with comparison with related experimental data, demonstrate that the model can be applied to study diffusion-induced fracture in general solid ionic conductors in Lithium-ion batteries. In particular, illustrative numerical results are presented for both the intergranular fracture inside active material or solid electrolyte and the interface fracture between active material and solid electrolyte. Furthermore, it is discussed how the solid electrolyte influences the dominant crack patterns. The current contribution is applicable to address similar problems on hydrogen-induced cracking and moister-dependent fracture.